Prevalence of human papilloma virus in Oman: Genotypes 82 and 68 are dominating. (April 2020) - Al-Lawati, Zainab; Khamis, Faryal A.; Al-Hamdani, Aisha; Al-Kalbani, Moza; Ramadhan, Fatma Ali; Al-Rawahi, Thuria Rashid; Al-Kobaisi, Muhannad F.
Highlights: Prevalence of Human Papilloma Virus in Oman was 17.8%. 22 different HPV genotypes were detected comprising 15 HR and 7 LR genotypes. Most frequently found was HR HPV 82 (10.77%) and LR HPV 54 (12.3) respectively. HPV in women with normal cytology was (17%) while with abnormal cytology (37.5%). Women with abnormal cytology showed HPV 82 more than other high-risk genotypes. Abstract: Background: Persistent infection with high-risk (HR) HPV genotypes has been associated with cervical cancer, the third cancer affecting women in Oman with a crude incidence rate of 4.7 and mortality rate of 2.5 respectively. Other types of lower-risk (LR) HPV are associated with warts in both genders worldwide. Objectives: To assess the prevalence and genotype distribution of HPV and the risk factors among women with normal and abnormal cytology. Methods: A cross sectional study conducted between September 2014 and April 2015. 258 cervical samples were obtained from women aged 18–68 years attending the Gynaecology Out-patient Clinic. HPV genotyping was performed using a multiplex real time-polymerase chain reaction (RT-PCR) assay. Results: 22 different HPV genotypes were detected in 46 women (17.8%) and included 15 HR and 7 LR genotypes. Human immunodeficiency virus (HIV) patients ( P = 0.052) and oral contraceptives users ( P = 0.016) showed significant association with HPV infection. Conclusion: The most frequently observed HPV types were HR HPV 82 and LR HPV 54. These findings show that the predominant HPV genotypes in Oman are different from those seen in worldwide studies. This finding is important to determine the potential impact of preventive measures especially new vaccines to reduce the burden of cervical cancer.